Modeling and Flexible Body Dynamics Analysis of Hemispherical Bevel Gears - Wang Baichao; Zhang Xue; Zhang Litong; Wang Cheng; Wang Jun; Yang Wenxiang; Sun Chenchen (Jixie chuandong)
In order to explore the influence of the variation of hemispherical bevel gear parameters on the dynamic characteristics of the system, a dynamic model of the hemispherical bevel gear pair is established based on the lumped mass method. Based on high-quality hexahedral mesh model, the dynamic transmission performance of hemispherical bevel gears is analyzed by rigid-flexible coupling flexible body dynamics simulation. The influence of parameters such as the size of hemispherical bevel gears and the shaft angle on the motion state of the system is analyzed. The simulation results show that the transmission accuracy, stability and strength of the system change regularly and are negatively correlated with each other under different parameters. The comprehensive performance of hemispherical bevel gears is the best when the diameter of indexing circle is 65 mm and the angle of intersecting shaft is 120°. The flexible multi-body dynamics simulation analysis provides an important reference for the model design, processing and manufacturing of hemispherical bevel gears.